Iodine(III)-mediated halogenations of acyclic monoterpenoids - Peilleron, Laure; Grayfer, Tatyana D.; Dubois, Joëlle; Dodd, Robert H.; Cariou, Kevin (Beilstein Journal of Organic Chemistry, 2018)
Five different halofunctionalizations of acyclic monoterpenoids were performed using a combination of a hypervalent iodine(III) reagent and a halide salt. In this manner, the dibromination, the bromo(trifluoro)acetoxylation, the bromohydroxylation, the iodo(trifluoro)acetoxylation or the ene-type chlorination of the distal trisubstituted double bond occurred with excellent selectivity and moderate to good yields.
Keywords: halogenation; hypervalent iodine; monoterpenes